2023
DOI: 10.3389/fpubh.2022.1109139
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of industrial agglomeration on industrial pollutant emissions: Evidence found in the Lanzhou–Xining urban agglomeration in western China

Abstract: Industrial agglomeration does not only promote economic and social prosperity of urban agglomeration, but also increases industrial pollution, which poses a health risk to the general public. The Lanzhou–Xining urban agglomeration in western China is characterized by industrial agglomeration and serious industrial pollution. Based on the county panel data of the Lanzhou–Xining urban agglomeration in western China from 2010 to 2018, a research of the impacts of industrial agglomeration on industrial pollutant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Several studies have revealed the association between cold environments and PM 2.5 pollution with a range of health problems, including cardiovascular diseases, respiratory diseases, and diabetes (4,5). In high-altitude areas, thin air, strong ultraviolet radiation, and increased human activities may have exacerbated the problem of air pollution in the environment (6)(7)(8). Studies have shown that air pollution in high-altitude regions has a significant impact on human health (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the association between cold environments and PM 2.5 pollution with a range of health problems, including cardiovascular diseases, respiratory diseases, and diabetes (4,5). In high-altitude areas, thin air, strong ultraviolet radiation, and increased human activities may have exacerbated the problem of air pollution in the environment (6)(7)(8). Studies have shown that air pollution in high-altitude regions has a significant impact on human health (9,10).…”
Section: Introductionmentioning
confidence: 99%